Community Service at Imam Syafi'i Islamic Boarding School - Panancangan- Cipocok Jaya- Serang City In The Implementation of Waste Processing Machinery & Digitalization of Accounting - Setiyawati, Hari; Arwati, I Gusti Ayu; Putra, Yananto Mihadi; Agustin, Andhika Permana; Sidik, Yusuf Samil (Ikatan Dosen Menulis, 2025)
The partner in this community service is the Imam Syafi'i Islamic Boarding School which is an Islamic educational institution located on Jl. Dishud / Fire Department, Km. 02, Panancangan Village, Cipocok Jaya District, Regency. Serang, Banten which is involved in the field of formal and non-formal Islamic education. Along with its development, the Imam Syafi'i Islamic boarding school continues to improve facilities for its students. And as students continue to increase, the daily food requirements are certainly quite large. This has an impact on increasing the amount of waste produced from kitchens or from school areas, where it would be very beneficial if this waste was recycled into useful goods or processed into fertilizer that can be used by oneself or sold to the community to increase income. The problems experienced by partners are: a). The partner in this community service is the Imam Syafi'i Islamic Boarding School which is an Islamic educational institution located on Jl. Dishud / Fire Department, Km. 02, Panancangan Village, Cipocok Jaya District, Regency. Serang, Banten which is involved in the field of formal and non-formal Islamic education. Along with its development, the Imam Syafi'i Islamic boarding school continues to improve facilities for its students. And as students continue to increase, the daily food requirements are certainly quite large. This has an impact on increasing the amount of waste produced from kitchens or from school areas, where it would be very beneficial if this waste was recycled into useful goods or processed into fertilizer that can be used by oneself or sold to the community to increase income. The problems experienced by partners are: a) Produce liquid fertilizer, b) Produce recycled products that are ready to use, c) Availability of an accounting application with features for SPP and cottage business units, namely Zahir Accounting. The targeted output is the Sinta Indexed National Scientific Journal/international journal, Articles in the mass media /print/electronic, Activity Videos, Increasing understanding and skills of boarding school administrators, students and ustadz and output of IPR (Creation Rights). Until now, the output that has been achieved is video. PKM activities have been implemented starting August 7 2024. All activities as targeted have been achieved 100%. To ensure the success of the program, evaluation will be carried out at each stage of program development. To support the success of this program, it will continue to be monitored and facilitated so that it can continue to be implemented consistently and developed according to needs.